Perovskite Puzzle for Revolutionary Functional Materials - Belich, Nikolai; Udalova, Natalia; Semenova, Anna; Petrov, Andrey; Fateev, Sergey; Tarasov, Alexey; Goodilin, Eugene (Frontiers in Chemistry, 2020)
Widely spread crystal lattices of perovskites represent a natural flexible platform for chemical design of various advanced functional materials with unique features. An interplay between chemical bonding, defects and crystallochemical peculiarities makes the perovskite structure a "lego designer" utilizing natural features of chemical elements of the renown Mendeleev's Periodic Table (PTE) celebrating 150 year anniversary. In this mini-review, crystal chemistry and bonding features, physical and functional properties, preparation methods and tuning functional properties with periodicity "tools" of the PTE will be exemplified for legendary families of high - temperature superconductive cuprates, colossal magnetoresistive manganites and hybrid lead halides for a new generation of solar cells.